Contents of sugars and organic acids in the cultivars of peach (Prunus persica L.) and nectarine (Prunus persica var. nucipersica Schneid.) - Mateja COLARIČ; Franci ŠTAMPAR; Metka HUDINA (Acta Agriculturae Slovenica)
The contents of sugars and organic acids in fruits were studied among 19 different peach and nectarine cultivars. The fruits were obtained from the Fruit Growing Centre Bilje near Nova Gorica in the time of technological maturity. Sugars (glucose, fructose, sucrose and sorbitol) and organic acids (citric, malic, shikimic and fumaric acid) in fruits were identified and measured by high performance liquid chromatography (HPLC). Sucrose was the major sugar and malic and citric acids were the predominant organic acids in all cultivars. The content of fructose ranged from 6.76 to 12.97 g/kg, glucose from 5.43 to 11.11 g/kg, sucrose from 46.14 to 70.7 g/kg and sorbitol from 0.40 to 2.80 g/kg of fruits. The content of citric acid was from 1.71 to 8.34 g/kg, malic acid from 3.2 to 8.05 g/kg, shikimic acid from 127 to 809 mg/kg and fumaric acid from 1.56 to 6.09 mg/kg of fruits. The content of total sugars was from 61.53 to 93.70 g/kg and the content of total organic acids was from 7.06 to 14.69 g/kg of fruits. We recommend cultivars ‘Françoise’, ‘Orion’, ‘Venus’, ‘Roza’ and ‘325 x A/8’ from the point of the content of sugars and organic acids and the optimal ratio between them.